Metabolic equivalent distance across game quarters and athlete position in female collegiate lacrosse players - Symons, B.; Bunn, J. (American Journal of Sports Science, 2024)
As a sport, field lacrosse requires seamless transitions between acceleration and deceleration. Unfortunately, linear displacement variables at a constant speed underestimate the energy demand in team sports, as they fail to account for the additional energy expended during acceleration and deceleration. In order to address these additional energy costs and offer a more precise measure of an athlete's workload, the metric called metabolic equivalent distance (MED) was developed. The purpose of the study was to assess the differences in MED across game quarters and athlete positions among female collegiate lacrosse players and determine potential relationships between MED and other workload variables. Seventeen female collegiate lacrosse players wore global positioning systems units, and data were collected over the course of 17 games. Performance variables were analyzed per minute played (min PT) and included: MED (m), total distance (m), accelerations (count), decelerations (count), total sprints (count), metabolic peak power (J), metabolic energy cost (J/kg/m), and equivalent distance index (%). No difference was found between athlete position. Performance variables did not differ between game quarters, except for playing time (p < .001). Athlete playing time was reduced in the 3rd and 4th quarters compared to quarter 1 (p < .001). MED showed a perfect correlation with total distance and metabolic energy cost (r = 1; p < .001) and a near-perfect correlation with accelerations and total sprints (r = .93; p < .001). Decelerations exhibited a strong correlation with MED (r = .86; p < .001). MED was moderately correlated with metabolic peak power (r = .34; p < .001); whereas equivalent distance index displayed a small correlation (r = .15; p = .02). Athletes exhibited a consistent output in metabolic workload variables across position and game per minute of play. MED could serve as a surrogate workload variable to better understand the athlete`s energy expenditure during high-intensity training and game play.